Pengaruh Kompetensi Komunikasi Politik Dan Manajemen Strategik Terhadap Kualitas Kader Partai - Sari, Ayu Puspita; Wijana, I Nyoman; Rasmini, Ni Wayan (Institut Agama Hindu Negeri Gde Pudja Mataram, 2024)
This quantitative study aimed to investigate how political communication competence and strategic management influence the quality of party cadres. The research goals included evaluating the levels of these competencies, assessing the quality of party cadres, and analyzing their impact on party quality. A sample of 103 participants completed questionnaires for data collection. The results showed that both political communication competence and strategic management had a significant impact on party cadre quality, with high ratings of 87.48% and 87.26% respectively. The overall quality level of party cadres, as assessed by the party, was 87.54%, indicating a very good standard. The statistical analysis confirmed that both competencies had significant effects on party cadre quality. This suggests that political parties should prioritize the development of political communication competence and strategic management among their cadres to improve party performance and public perception.